Taḥlil Akhto’ Nuṭq al-Salâm li Tullâb al-Madrasah al-Dîniyyah wa Tanfîżihi fî Ta’lîm al—Lugah al-Arabiyyah - Faiqotussana; Tulus Musthofa; Nailin Najihah; Binti Roifatus Siam; Nasiruddin (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Purpose- This study aims to analyze the errors in pronunciation of Arabic greetings (salam) to students of Madrasah Diniyyah Assalam Tegalombo Class VI and find out the implementation in Arabic learning. Design/Methodology/Approach- This study used a descriptive qualitative method using a contrastive analysis approach. The validity of the data was tested by using triangulation technique. The data were obtained through field research. Findings- Based on the results of the research on errors in pronunciation of Arabic greetings to Class VI students of Madrasah Diniyyah Al-Quran (MDA) Assalam Tegalombo consisting of 16 students, it was found 7 forms of pronunciation that were not in accordance with the original phonology of salam, example Assalamualaikum, Salamualaikum, Slamualaikum, Slamlékum, Saamlékum, Samlékum, and Smléikum. Of the 7 forms of pronunciation errors, there are 4 types of phonological errors, namely 1) Pronouncing "ع" to "أ" because the mother tongue does not have these consonants. 2) Pronouncing the wrong word structure because of al-akhtho 'al-syâi'ah. 3) The sound /ai/ becomes /é/ due to socio-cultural factors. 4) Do not extend consonant lam because the mother tongue does not have mad. The implementation is that in the future Arabic language teachers for foreign speakers can put more emphasis on the phonological aspect. Because in Arabic, different pronunciations and pronunciations will produce different meanings. Research Limitation/Implications- The limitations of the problem in this study focused on the pronunciation of the greetings of students at Madrasah Diniyyah Al-Quran (MDA) Assalam Tegalombo class VI. However, this study has not examined further about the mispronunciation of the greeting answers.